Future Forecast of The Area and Production of Irrigated Wheat in Daraa Governorate Using The ARIMA Model Summary (Damascus University Journal of agriculture sciences, 2022)
The research aims to analyze the time series related to the area and production of irrigated wheat in Daraa governorate, between 1990-2018 in order to estimate a model that helps predicting, planning, and drawing production policies, using Box-Jenkins methodology and ARIMA models, which combine the self-regression and average methods Time series moving, as this model is characterized by high accuracy and flexibility in analyzing time series. Statistical methods related to time series have been applied. Stability tests were performed using the Dicky - Fuller test ADF, and using the autocorrelation function parameters ACF, and the partial autocorrelation PACF.The results of the analysis show that the time series: ARIMA (1, 1, 0) ARIMA (1,1) is the best model for predicting the area and production of irrigated wheat crop in the study area, based on the results of the autocorrelation and partial self-correlation functions and the used statistical criteria. It is expected that both the area planted with the irrigated wheat crop and the production in 2023 will increase by about 0.46% and 5.06% each, respectively, compared to 2018.
Keywords: time series; irrigated wheat; Box-Jenkins methodology; ARIMA models.